The Return of England in English Literature - Gardiner, M. author. aut Link
VI, 211 p.
Keywords: This lively study provides an account of the 'fall and rise' of the English nation within the British discipline of English Literature between the late eighteenth century and the present day, offering a reconceptualisation of the relationship between English Literature and the formation of English cultural identity.